Improvement of ankle foot orthotics fabrication using 3D printing method - Saptaji, Kushendarsyah; Manasikana, Dinda Arina; Juniasih, Octarina Adiati; Ramadhani, Mochammad Rafli; Oktaviandri, Muchamad; Ramadhan, Anwar Ilmar; Asmara, Yuli Panca (SINERGI, 2024)
Orthotics are the body support devices used for correction, immobilization, fixation, and prevention of paralysis. The greatest number of orthotics utilized by people suffering from plantarflexion and dorsiflexion disability, especially in Indonesia, is ankle foot orthotic (AFO). However, the duration associated with fabricating AFO through conventional methods is considered time-consuming. This paper aims to fabricate ankle foot orthotics (AFO) using innovative combinations of 3D scanning and 3D printing. The method begins with 3D scanning of the patient’s lower limb using photogrammetry (3DF Zephyr). The design is generated and adjusted, afterwards, the orthotic prototype is produced by fused deposition modeling (FDM) 3D printing using polypropylene (PP) material. This choice is attributed to the material's advantages, such as being lightweight, rigid, durable, and cost-effective. The 3D mesh model scanned using 3DF Zephyr shows good quality and more precise results. In addition, the prototype produced using 3D printing was tested by walking based on normal gait analysis’s angle of foot and calf measurement, which shows a maximum range of motion (ROM) of 16.1˚. The proposed methods of fabricating orthotic prototypes can successfully reduce the processing time by approximately 70% compared to the conventional method.